Accessible Phreatic Groundwater Resources in the Central Shijiazhuang of North China Plain: Perspective From the Hydrogeochemical Constraints - Xiao, Yong; Xiao, Dian; Hao, Qichen; Liu, Kui; Wang, Rui; Huang, Xun; Liao, Xin; Zhang, Yunhui (Frontiers in Environmental Science, 2021)
Phreatic groundwater plays significant role in water supply for human community, especially in water scarce regions. This research was conducted to investigate the hydrochemistry and contamination of phreatic groundwater and their constraints on drinking water supply in a semiarid region of North China Plain. A total of 49 phreatic groundwaters were collected for the hydrochemical analysis. The results suggested the phreatic groundwater had a slightly alkaline nature. Although the groundwater had a large variation of salinity with the TDS of 172-1875 mg/L, most groundwater was moderately-hard fresh and of HCO3-Ca type. Contaminants of NO3-, NO2-, NH4+, Fe, F-, Zn, Mn were detected, but only NO3-, NO2-, NH4+ and Fe were found exceeding the drinking water desirable limits at some sites. Groundwater hydrochemical components were naturally originated from Silicates weathering, dissolution of sulfates and carbonates, as well as ion exchange. The nitrogen contaminants were from anthropogenic inputs (urban sewage effluents and agricultural fertilizers) and mainly distributed in the central study area. The anthropogenic inputs of nitrogen contaminants also elevated groundwater salinity. Among the exceeding contaminants, only NO3- would pose potential health risk to water consumers. The existing health risks by NO3- ranged from medium risk (HQ of 1-4) to high risk (HQ＞4) for all populations, and most risks were categorized into the medium risk rank. Groundwater F- was also found with health risk at some sporadic sites although it did not exceed and only approach to the desirable limit. Its health risk was only to infants and categorized into the medium risk with the maximum HQ of 1.55. Most phreatic groundwater (83.67%) in the study area had relatively good quality and suitable for domestic usage with the EWQI value below 150. Others belonged to the poor (EWQI of 150-200) and extremely poor (EWQI＞200) quality categories, and mainly distributed in the urban Gaocheng. These poor quality groundwater should be avoid being directly used for domestic purposes. Sewage effluents in the urban Gaocheng and fertilizers in agricultural lands should be concerned and controlled to safeguard the clean phreatic groundwater resources in the study area and other similar regions worldwide.